Empirical Analysis On Factors Influencing Customer Loyalty In Malaysian Telecommunication Industry - Ismail, Hishamuddin (2007)
This study has been designed to asses and propose the appropriate customer loyalty model that would likely to fit in the competitive environment of the telecommunication industry. The study will be focusing on the telecommunication industry since this industry will play a pivotal role in the information technology (IT) era.